Indian Personal Law and Women’s Rights - Das, Satarupa; Athwaite, Rashmi (Journal of Social Science and Humanities, 2024)
Women rights are undeniably connected to personal laws, the Indian Constitution, and other particular laws in a multi - religious country like India. From an equality point of view, the personal law system in India is perceived as problematic since it provides for different laws for different communities. Also women under the attire of religion are often discriminated against in the matters of divorce, maintenance, inheritance etc. In such situation, the introduction of uniform civil code is thought to be a path towards gender justice securing rights of women. This paper shall examine different personal laws vis - a - vis women rights and whether UCC in India will be a boon or bane for women rights.